Cartilage tissue and knee joint biomechanics : fundamentals, characterization and modelling - Nochehdehi, Amirsadegh Rezazadeh; Nemavhola, Fulufhelo; Thomas, Sabu; Maria, Hanna J. (Academic Press, an imprint of Elsevier, 2024)
Cartilage, Tissue and Knee Joint Biomechanics: Fundamentals, Characterization and Modelling is a cutting-edge multidisciplinary book specifically focused on modeling, characterization and related clinical aspects. The book takes a comprehensive approach towards mechanics, fundamentals, morphology and properties of Cartilage Tissue and Knee Joints. Leading researchers from health science, medical technologists, engineers, academics, government, and private research institutions across the globe have contributed to this book. This book is a very valuable resource for graduates and postgraduates, engineers and research scholars. The content also includes comprehensive real-world applications. As a reference for the total knee arthroplasty, this book focuses deeply on existing related theories (including: histology, design, manufacturing and clinical aspects) to assist readers in solving fundamental and applied problems in biomechanical and biomaterials characterization, modeling and simulation of human cartilages and cells. For biomedical engineers dealing with implants and biomaterials for knee joint injuries, this book will guide you in learning the knee anatomy, range of motion, surgical procedures, physiological loading and boundary conditions, biomechanics of connective soft tissues, type of injuries, and more.